Learning Innovation Of Islamic Religious Education Based On Problem Based Learning - Lukman Hakim (Jurnal Scientia, 2021)
Currently, the ongoing teaching and learning process is still dominated by a conventional method and states that knowledge is a fact that must be memorized. Therefore, most of the situations in the classroom still focus on the teacher (teacher centered) as the main point of knowledge. Such a learning situation certainly does not involve students in developing problems. To develop an innovative and creative teaching and learning climate, it is very necessary to have a link between educational components such as teachers and students. So that the educational components can work together to create a conducive learning process, Problem Based Learning is the right choice, because students are required to get solutions to the problems they get in groups so that knowledge exchange can occur, either between students or teachers to students. The purpose of this study is to describe the role of model based learning in Islamic religious education so that the values of Islamic religious education can be applied in everyday life. The research method used in this study is descriptive research and uses a qualitative approach and then analyzed using phenomenology by drawing conclusions based on the data obtained and in accordance with the objectives of the study.